(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
This article deals with the themes of Cuban identity and death in the poem “La isla en peso” by the Cuban writer Virgilio Piñera. It is a reading which deliberately focuses on thematic aspects, though it doesn’t exclude approaches to the formal or compositional levels. Piñera’s strategy frames or reveals the lyric subject’s point of view, responding to a tension between the “self” and the “other” which never finds definitive resolution and represents the central discursive mechanism of what we will call here the ’rhetoric of silence’, contrary and complementary to the other, the ’rhetoric of emphasis’.